Meat productivity and beef quality of Black-and-White bulls fed with zinc and selenium in organic form as part of the diet - A. V. Kharlamov; A. N. Frolov; V. V. Ilyin (Аграрная наука Евро-Северо-Востока, 2024)
Increasing the production of high quality ecologically pure animal products, especially beef is one of the main tasks of the agro-industrial complex. In this regard, it is necessary to apply measures for the effective use of genetic resources of both domestic and imported origin, improving feeding systems, using feed additives, biological active substances that stimulate the growth and development of animals. The aim of the study was to determine the effect of the feed additives Plexomin Zn 26 and Plexomin Se 2000, containing in its composition zinc and selenium in organic form, on the slaughter parameters of Black-andWhite bulls, as well as on the quality of the obtained product - beef. For the research, 15-month-old Black-and-White bulls were divided into two groups (control and experimental) of 20 heads each, average live weight was 328.8–329.3 kg. The experiment lasted 91 days. The difference was that the experimental animals were fed with the feed additives Plexomin Se 2000 at a dosage of 1.2 g/head/day and Plexomin Zn 26 at a dosage of 1.2 g/head/day as part of the concentrated part of the diet during the study period. A control slaughter was carried out at the meat processing plant "Orenbeef" for comparative evaluation of meat productivity and beef quality of bulls fattened with and without feed additive. As a result of the research, it was found out that experimental bulls outperformed their control counterparts in live weight at the end of the experiment by 2.5 % (Р≤0.05), pre-slaughter live weight by 2.2 % (Р≤0.05), fresh carcass weight by 4.5 % (Р≤0.01), internal fat weight by 22.1 % (Р≤0.05), slaughter weight by 5.2 % (Р≤0.01), and slaughter yield by 1.62 % (Р≤0.05). Meat from experimental bulls contained 1.35 % more dry matter (Р≤0.05), 0.26 % more fat (Р≤0.05), 32.9 % more glycogen (Р≤0.01), 1.3 % less moisture (Р≤0.05), 7.1 % more oxyproline (Р≤0.05) and 1.92 % more pH (Р≤0.05).